2011
DOI: 10.1021/ol200808q
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Deoxyfluorination of Catechols

Abstract: Nucleophilic deoxyfluorinaiton of one of the two hydroxyl groups of catechols has been developed via the Umpolung concept. This method was successively applied to naturally occurring catechols, such as catechins and dopamine, to produce novel fluorinated analogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 43 publications
3
29
0
2
Order By: Relevance
“…Akai et al also reported an example of nucleophilic deoxyfluorination with catechols (Eq. 18) [42]. Through umpolung reactivity, one hydroxy group of the catechol is fluorinated, affording a variety of fluorinated phenol isomers.…”
Section: Nucleophilic Deoxyfluorinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Akai et al also reported an example of nucleophilic deoxyfluorination with catechols (Eq. 18) [42]. Through umpolung reactivity, one hydroxy group of the catechol is fluorinated, affording a variety of fluorinated phenol isomers.…”
Section: Nucleophilic Deoxyfluorinationmentioning
confidence: 99%
“…Rhodium silyl complexes having different R groups, RhSi(OR) 3 (PEt 3 ) 3 ; R ¼ Me, Et, were found to activate hexafluorobenzene and perfluorotoluene giving (39) and (40) (Scheme 17). The fluorinated heterocycles, 1,2,4,5-tetrafluoropyridine and pentafluoropyridine, also underwent C-F activation at the 2-position affording (41) and (42). DFT calculations suggested C-F activation is assisted by the silyl group showing preference for activation in the 2-position.…”
Section: ð39þmentioning
confidence: 99%
“…Catechol moieties can be monodeoxyfluorinated by oxidation of catechol to the orthoquinone followed with fluorination with Deoxo-Fluor®, which gives an unselective mixture of fluorinated products. 182 Deoxyfluorination of para-nitrophenol with N,N′-dimethyl-2,2-difluoroimidazolidine 12a led to the development of a general method for the ipso-deoxyfluorination of phenols with commercially available PhenoFluor™ and cesium fluoride (Scheme 56). 12b Electronpoor, -neutral, and -rich phenols as well as hydroxypyridines can be transformed to the corresponding aryl fluorides.…”
Section: Phenol Deoxyfluorinationmentioning
confidence: 99%
“…Unauthorized distribution is strictly prohibited. LETTER Synlett 2012, 23, 1978-1984 The subsequent reduction of the crude products by NaBH 4 (5 equiv) afforded the desired ortho-fluorophenols 7a-g as the major products along with their regioisomers 4a-g (Table 4, entries [7][8][9][10][11][12][13]. 30 In summary, we have developed the complementary synthesis of two kinds of fluorinated bridged biphenyls 4 and 7.…”
Section: Scheme 3 Deoxyfluorination Of 2 Andmentioning
confidence: 99%
“…Other ethereal solvents, such as THF, dioxane, and Et 2 O, were also available for producing 2a, albeit in lower yields (Table 1, entries [6][7][8]. The dienone-phenol rearrangement of 2a took place to quantitatively give the bridged biphenyl 5a by the treatment with MsOH (1 equiv) at 80 °C for 24 hours.…”
mentioning
confidence: 99%